2019
DOI: 10.3389/fpsyg.2018.02772
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Temporal Theory to the Field of Sport Psychology: Toward a Conceptual Model of Time Perspectives in Athletes’ Functioning

Abstract: Time perspective theory provides a robust conceptual framework for analyzing human behavior in the context of time. So far, the concept has been studied and applied in multiple life domains, such as education, health, social relationships, environmental behavior, or financial behavior; however, its explanatory potential has been completely neglected within the domain of sport. In the present paper we provide a deepened theoretical analysis of the potential role of temporal framing of human experience for sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 106 publications
(185 reference statements)
0
11
0
Order By: Relevance
“…It was expected that the time perspectives of the elite and non-elite athletes were different since they arise out of personal and social experience (Zimbardo and Boyd, 2008 ), and their engagement in sports is certainly significant experience for both groups of the athletes examined. The assumed model of the effects of time perspectives on sports engagement (Stolarski et al, 2019 ) suggested that past positive time perspective would have positive effects, either directly or indirectly, and past negative time perspective would have adverse effects on sport performance. The results obtained in this study have supported this assumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was expected that the time perspectives of the elite and non-elite athletes were different since they arise out of personal and social experience (Zimbardo and Boyd, 2008 ), and their engagement in sports is certainly significant experience for both groups of the athletes examined. The assumed model of the effects of time perspectives on sports engagement (Stolarski et al, 2019 ) suggested that past positive time perspective would have positive effects, either directly or indirectly, and past negative time perspective would have adverse effects on sport performance. The results obtained in this study have supported this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results which are inconsistent with the assumed model were also obtained in this research. Present fatalistic time perspective has shown to be more present in the elite athletes and it was expected to have negative effects on a motivation-engagement-performance chain (Stolarski et al, 2019 ). The obtained data is unexpected when we take into account that people with fatalistic understanding of the present have, amongst other things, reduced personal efficiency, external locus of control and planning, which should be accompanied by effort and work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, applying the SES to individuals with various levels of exercising habits would provide further evidence for the scale's validity and broaden the findings reported in the present paper. The construct of sport engagement should also be closely investigated in relation to actual sport performance in sport disciplines other than running, with both direct and indirect mechanisms of influence being distinguished (see Stolarski et al 2019). Finally, it would be beneficial to examine the measurement invariance of the construct across different sports.…”
Section: Discussionmentioning
confidence: 99%
“…Motivational and cognitive components, objectives, their significance, personal beliefs, emotional resources were discussed during pauses. Psychological assessments of the state perceived by athletes were determined by athletes' interpretation of the efficiency of achievement drive; similar practice is known [16].…”
Section: оRganization Of Studymentioning
confidence: 99%